Impact of Railway Investment on Regional Development – Case Study of Pomeranian Metropolitan Railway - Cezary Mankowski; Dariusz Weiland; Borna Abramović (Promet - Traffic&Transportation, 2019)
From the regional development point of view new investments are always of great importance as they are mainly expected to boost the regional economy and thus improve the living standard of inhabitants. Also for the literature purposes a new case study on the impact of investments on regional development can be perceived as an added value to the state of the art and thus worthy to be explored. In this research the impact is measured in the following aspects: social, economic, innovation, and environmental, which stand also for the main assessment criteria. Just recently, an opportunity has appeared to explore this subject on the Pomeranian Metropolitan Railway (PMR), which started its operations on 1st September 2015, after five years of construction works and more than a 100-year long history. Thus, the paper presents the impact results of PMR on the development of the Pomeranian region, in the form of qualitative as well as quantitative assessments in the four aspects and on different levels of detail. The final conclusion states that the impact of PMR on the regional development has appeared to be negative in 33% and positive in 67%.